2004
DOI: 10.1093/ndt/gfh123
|View full text |Cite
|
Sign up to set email alerts
|

Paricalcitol-treated patients experience improved hospitalization outcomes compared with calcitriol-treated patients in real-world clinical settings

Abstract: Paricalcitol-treated patients experienced fewer hospitalizations and hospital days per year when compared with calcitriol-treated patients. Initiating vitamin D therapy with paricalcitol may result in overall savings of approximately 7600-11,000 US dollars per patient per year. A randomized, controlled, blinded study would be valuable in confirming and understanding these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 15 publications
3
64
0
6
Order By: Relevance
“…The small mean decrease in calcium observed in the placebo group is consistent with the pathogenesis of SHPT and VDR inactivation and reflects the disease state in this population. Tissue and gene selectivity of paricalcitol thus allows for a greater therapeutic index for PTH reduction and may explain the previous observations of improved survival [16] and reduced morbidity [19]. …”
Section: Discussionmentioning
confidence: 92%
“…The small mean decrease in calcium observed in the placebo group is consistent with the pathogenesis of SHPT and VDR inactivation and reflects the disease state in this population. Tissue and gene selectivity of paricalcitol thus allows for a greater therapeutic index for PTH reduction and may explain the previous observations of improved survival [16] and reduced morbidity [19]. …”
Section: Discussionmentioning
confidence: 92%
“…An important observation in these studies was the fact that a survival benefit of VDRA was apparent across all quintiles of calcium, phosphate and PTH, which suggests that the use of vitamin-D receptor activators may possibly mitigate the deleterious effects of elevated phosphate, calcium and PTH on mortality (16,17). Both the mortality and morbidity data from these studies suggest that the benefit of paricalcitol was independent of baseline PTH, calcium or phosphorous levels, as a reduction in the risk of both death and the number of hospital admissions was apparent at all levels, when the data was stratified by variables (16)(17)(18). In contrast, data from the Dialysis Outcomes Practice Patterns Study (DOPPS) and from a notfor-profit dialysis provider in the United States demonstrated that differences in mortality risk between different vitamin-D receptor activators may be smaller than previously reported and that a prospective randomized controlled clinical trial is both needed and justified (19,20).…”
Section: Discussionmentioning
confidence: 91%
“…These results were reproduced in other studies. 11,14 It has been shown that paricalcitol treatment may be associated with lower mortality, 20 lower hospitalization rates, and in-hospital stay 21 compared with calcitriol treatment. These beneficial effects on hard outcomes may not be related only to effects on calciumphosphorus metabolism but also depend on postreceptor differences between the molecules.…”
Section: Discussionmentioning
confidence: 99%